1990
DOI: 10.1038/bjc.1990.411
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of a hypoxia marker in spontaneous canine tumours

Abstract: An immunoperoxidase technique has been used to detect the in vivo binding of a 2-nitroimidazole hypoxia marker in histochemical sections of a variety of excised canine tumours. The binding occurred 10-12 cell diameters away from tumour blood vessels, consistent with the expected location of hypoxic cells in tissues in which oxygen concentration gradients are established by diffusion. Hypoxic fractions ranging from 4 to 13% have been estimated on the basis of morphometric analysis of multiple tumour sections. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Immunohistochemical studies of patterns of tumour hypoxia, using hypoxia marker drugs, in canine and human tumours have typically reported that most intense binding occurs near regions of necrosis, which are typically farthest removed from the nearest microvessel (Cline et al, 1990;Kennedy et al, 1997). Immunohistochemical localization of microvessels would help to clarify this issue further because it is frequently difficult to positively identify microvessels on the basis of H and E staining alone.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies of patterns of tumour hypoxia, using hypoxia marker drugs, in canine and human tumours have typically reported that most intense binding occurs near regions of necrosis, which are typically farthest removed from the nearest microvessel (Cline et al, 1990;Kennedy et al, 1997). Immunohistochemical localization of microvessels would help to clarify this issue further because it is frequently difficult to positively identify microvessels on the basis of H and E staining alone.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit polyclonal, anti-pimonidazole antisera used in the calibrated ELISA were prepared and characterised in a manner analogous to that for CCI-103F -a 2-nitroimidazole compound with six fluorine atoms on the sidechain (Raleigh et at., Cline et al, 1990 Immunohistochemical patterns ofpimonidazole binding in liver As expected, immunostaining in livers perfused at low flow rates in the anterograde direction was localised in oxygenpoor, centrilobular regions ( Figure 3a). The pattern of immunostaining was reversed in liver perfused in the retrograde direction; that is, the staining was now localised in the oxygen-poor, periportal region of the tissue (Figure 3b).…”
mentioning
confidence: 99%
“…Hydroxyprobe is an exogenous nitroaromatic compound [1-[(2-hydroxy-3-piperidinyl)propyl]-2-nitroimidazole hydrochloride] frequently used to study hypoxia in cancer (27)(28)(29).…”
Section: Phenotypic Histological and Immunohistochemical Examinatiomentioning
confidence: 99%